Penyelamatan Ternak pada Bencana Banjir (Studi Kasus Kecamatan Trucuk-Kabupaten Bojonegoro) - Purwitasari, Ony (Jurnal Manajemen Bencana (JMB), 2019)
Experience of Merapi Eruption in 2010 has been the background of this research, in which disaster management actors realized that not only should the human be saved but also the livestocks. This research is about the effort of local government and community in Bojonegoro District on livestock rescue at Bengawan Solo flood using qualitative research method. This research aims to analyze livestock rescue performed by community and analyze the effective system of livestock rescue by local government in accordance with the pattern of livestock rescue by community. The results are in follows: 1) the community has had the understanding of Bengawan Solo flood’s characteristics and local wisdom of livestock rescue effort; 2) The effort done by the local government is to fill the gap in which community is not able to cope with. Interventions conducted by the local government are veterinary support, livestock shelter and settlement on early phase. The recommendation of this research is the community has to have caution and keep remembering that they are living in the disaster hazardous zone. Local wisdom of community becomes capital for local government to conduct community based livestock rescue program. There is also a need assessment and intervention of post flood veterinary support, assessment of feed supply as well as the follow up of livestock shelter and settlement intervention and also need to develop livestock emergency guideline for Indonesia context